COPING STRES ANAK KORBAN BROKEN HOME (STUDI KASUS SANTRI PONDOK PESANTREN DARUSSALAM PUTRI UTARA) - M. Rizqon Al Musafiri (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This research is motivated by the problem of stress experienced by children who are victims of broken homes. a hope of a child who wants his parents intact like his friends and can enjoy the love of his father and mother has never been obtained by a child who is a victim of a broken home. This makes children feel disappointed and jealous of their friends. The focus of research in writing this thesis is what are the sources of stress experienced by children who are victims of broken homes and how to cope with stress strategies for children who are victims of broken homes. The purpose of this study is to determine the source of stress for children who are victims of a broken home and to find out the coping stress of children who are victims of a broken home.In this research, the type of research used is descriptive qualitative research. Data collection methods used are observation, interviews and documentation. The results showed that the cause of the subject's stress was psychological stressor, which was caused by deep disappointment due to divorce and pressure from his father who did not allow him to meet and relate to his mother. The stress coping used by the subject is coping that focuses on emotions (Emotion-Focused Coping). namely Escape avoidance (avoiding themselves) because when the subject of the Islamic boarding school vents to all activities such as lazy to study and interact with his friends. Even the subject prefers to sleep and ignores everything. The subject also raises Positive reappraisal behavior (giving positive values) to divert problems that always disturb his mind, the subject chooses to involve himself in religious matters, namely memorizing the Qur'an to get closer to Allah SWT.